New discovers of eight poets from Kâzeroun - عبدالرسول فروتن; منصور طباطبایی (تاریخ ادبیات)
In this paper, we use some manuscripts – ‘Jong’s and ‘Tazkare’s that not pressed – to give new information about biography and poems of eight unknown poets from Kâzeroun in Fârs province. Some of this poets didn’t introduction yet and from other poets we had infrequent couples or nothing; so in this article we completed this information. One of this poets – Jamâlâ – wrongly Supposed as three poet; but in this paper we found that this three poem is one. This eight poets that we discussed about them is: Arshad (centuries 9 & 10 AH), Jamâlâ (centuries 10 & 11 AH), Raf’at (before 12 century), Sheikh-ol Hokamâ (Defunct 1334 AH), Novbahâr (centuries 13 & beginning of 14 AH), Jonouni-e Korrâei (Defunct 1094 AH), Ja’fari (before 12 century) and Khatib-e Kâzerouni (9 Century).